On the function of guard cell transporters in the response of Arabidopsis thaliana to changes in CO2 and water availability - Luz, Luana Moraes da (2019)
Plants represent the major sources worldwide of human foods and livestock feeds. Thus, future food security will clearly depend on how plant species respond to global environmental changes. Increases in carbon dioxide concentration [CO 2 ] in the atmosphere and fluctuations in rain patterns are amongst the main climate changes affecting crop yield. Notably, crop yield decreases under drought, yet elevated [CO 2 ], when associated with drought, may mitigate the negative effects of drought. Among the physiological effects of elevated [CO 2 ], partial stomatal closure and synergistically increased water use efficiency (WUE), leading to higher growth, are usually observed. However, either higher growth or survival of plants under high [CO 2 ] will directly depend on the degree of water availability into the soil. Water losses are controlled directly by the stomata, functionally specialized microscopic pores in leaf surface, that regulates the flow of gases between plants and atmosphere. Accordingly, stomata are the key entry point for CO 2 assimilation and water losses, controlling the essential exchange of CO 2 and H 2 O with the environment in land plants. Stomatal movements occur in response to the activation and inactivation of membrane proteins present in the guard cells. The relationship between stomatal aperture and photosynthesis/transpiration is linear over a wide range of environmental conditions. Thus, a better understanding of stomatal regulation by environmental stimuli represents an important step for developing plants in which WUE and photosynthesis capacity are optimized, once the maintenance of photosynthesis, one of the main events of the primary metabolism, and its capacity may directly influence crop yield. This thesis is largely focused on the role of proteins involved in the stomatal movements in response to changes in both [CO 2 ] and water availability. To this end, two stomatal proteins in Arabidopsis thaliana, namely the slow-type anion channel (SLAC1) and the ATP-binding cassette B14 transporter (ABCB14) were used to further investigate the duality of the efficiency between the CO 2 influx and the water efflux by the stomata under elevated [CO 2 ] and water limitation. SLAC1 is considered a key protein for stomatal closure in response to drought and [CO 2 ], while ABCB14 is the sole influx transporter of malate of the guard cell and is only responsive to increased CO 2 . The main goal of this study is to increase our understanding of the stomatal regulation in response to a realistic future climate change scenario using a metabolic, physiological, anatomical and molecular characterization of mutant plants with opposite stomatal responses. First, our results demonstrated that slac1 mutant plants are seemingly constantly under stress effect, regardless of the water restriction, since to sustain the increased stomatal conductance (g s ) slac-1 mutant plants display an elegant metabolic reprogramming that is apparently crucial for growth survival under moderate water limitation. Here we further hypothesized that ABCB14 may play an important role while allowing a modest stomatal opening that may be essential for continuity of gas exchanges under high [CO 2 ] conditions. In the second part, it was demonstrated that despite the reductions in the stomatal opening, the absence of a functional guard cell ABCB14 protein does not compromise overall photosynthetic activity and growth and that an exquisite metabolic and genetic regulation occurs in guard cells likely compensating, at least partially, the functional lack of abcb14. The data obtained here are discussed in the context of the role of each guard cell transport both generally to guard cell and photosynthetic metabolism and specifically with respect to its function in the regulation of stomatal aperture.